Cast out : vagrancy and homelessness in global and historical perspective - Beier, A. L.; Ocobock, Paul, 1980- (Research in international studies. Global and comparative studies series, 2008)
Throughout history, those arrested for vagrancy have generally been poor men and women, often young, able-bodied, unemployed, and homeless. Most histories of vagrancy have focused on the European and American experiences. Cast Out: Vagrancy and Homelessness in Global and Historical Perspective is the first book to consider the shared global heritage of vagrancy laws, homelessness, and the historical processes they accompanied. In this ambitious collection, vagrancy and homelessness are used to examine a vast array of phenomena, from the migration of labor to social and gov.